Monitoring the Light‐induced Isomerisation of the Prototypical Polycyclic Aromatic Hydrocarbons C10H8+ through Ion‐Molecule Reactions. Issue 2 (25th October 2022) - Jacovella, Ugo; Rossi, Corentin; Romanzin, Claire; Alcaraz, Christian; Thissen, Roland
Abstract: Structural rearrangements in ions are essential for understanding the composition and evolution of energetic and chemically active environments. This study explores the interconversion routes for simple polycyclic aromatic hydrocarbons, namely naphthalene and azulene radical cations (C10 H8 + ), by combining mass spectrometry and vacuum ultraviolet tunable synchrotron radiation through the chemical monitoring technique. Products of ion‐molecule reactions are used to probe C10 H8 + structures that are formed as a function of their internal energies. Isomerisation from azulene radical cation towards naphthalene radical cation in a timescale faster than 80 μs was monitored, whereas no reverse isomerisation was observed in the same time window. When energising C10 H8 + with more than 6 eV, the reactivity of C10 H8 + unveils the formation of a new isomeric group with a contrasted reactivity compared with naphthalene and azulene cations. We tentatively assigned these structures to phenylvinylacetylene cations. Abstract : Chemical monitoring technique is used to delve into the structural diversity of C10 H8 +, illustrating the chemical role of isomers that are not necessarily the most thermodynamically stable ones. These peculiar isomers will drive unexpected chemistry in energetic media such as flames, plasmas, and the interstellar medium.